Desorption of Naphtol Blue-Black from Humic Acid Modified Magnetite Using NaOH as Desorption Agent - Putri, Nunung Faizah Yosi; Rahmayanti, Maya (Proceeding International Conference on Science and Engineering, 2020)
Naphtol blue-black was a waste that is dangerous for the environment. The research aims to determine the effect of varied concentration of the NaOH as desorption agent on the percent of desorption of naphtol blue-black from humic acid modified magnetite (Fe3O4-AH). The result of this study showed that the variation of the NaOH concentration influenced the percent of naphtol blue-black desorption from humic acid modified magnetite. The percent of desorption was 15.71 % with a concentration of NaOH was 1 M.